Determinants of corporate dividend policy: a Malaysian perspective - Wan Abdullah, Wan Razazila; Ismail, Norashikin; Mohamed Sadique, Raziah Bi (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2005)
This study attempts to contribute to a debate on the issue of dividend policy by examining the determinants of dividend policy for companies listed on the Main Board of Bursa Malaysia. A sample of 174 firms was selected for the period 1999 to 2004. The financial data of these companies was analysed by regressing the leverage, profitability, tangibility, size, growth, and liquidity to the dividend payout. Based on the pooled results, size and growth have a significantly positive relationship with dividend payout, while leverage has a significantly inverse relationship with dividend policy. Also, a further study was conducted to determine which financial variables affect dividend payout for different industries. For industry analysis, size has a significantly positive relationship with dividend payout ratio for certain industries like Industrial Products, Consumer Products, Real Estate/Properties and Hotel and Infrastructure. Furthermore, debt is a variable that has a significantly negative association with the dividend payout ratio for Industrial Products, Consumer Products, Construction and Real Estate/Properties companies.